Amino acid functionalized blue and phosphorous-doped green fluorescent carbon dots as bioimaging probe1. Issue 81 (3rd September 2015) - Sarkar, Saheli; Das, Krishnendu; Ghosh, Moumita; Das, Prasanta Kumar
<x xml:space="preserve">Abstract</x> Thermal coupling between citric acid and Na-salt of glycine, l-valine and l-isolucine produced blue emitting carbon dots (CDs) and in presence of NaH2PO4, produced green emitting phosphorous doped CDs (PCDs), which were utilized for cell imaging.